Learning environments of technology supported secondary science classrooms: a study in an Indian school - Gupta, Adit (Curtin University, 2007)
Science teaching at the secondary level can be made more effective with the judicious utilization of a multi-media approach involving modem information and communication technologies that is entering the Indian educational system in general and the schools in Jammu region (J&K State), in particular, surely but slowly. A major impact of technology today in the field of education is that at all levels classrooms are becoming technology-rich learning environments and as such there is a need to conduct research to study the learning environments of technology-supported classrooms. The study described in this thesis utilized the Technology-Rich, Outcomes-Focused Learning Environment Inventory (TROFLEI), to study the perceptions of students' actual and preferred classroom learning environment in a technology-supported science classroom at the secondary level in an Indian school situation. An important aspect of this research was to determine the reliability and validity of this scale for use in Indian classroom settings. An attitude scale derived from the Test for Science Related Attitudes (TOSRA) for studying the attitude of students towards science was also employed and lastly the Questionnaire on Teacher Interaction (QTI) was used to analyze the teacher student interactions in a technology-supported science classroom environment. Data for research were collected from 700 secondary students in a co-educational Indian school in the city of Jammu.The study reported that the TROFLEI and the QTI were reliable and valid instruments for assessing the psychosocial learning environments III a technology-supported classroom and the teacher-student interactions III such environments. Significant associations are also reported between the students' perceptions of their technology-supported learning environment and their perceptions of the teacher-student interactions with three learner outcomes; attitude towards science, academic efficacy and academic achievement. Significant gender differences in technology-supported learning environments have also been reported in this study. This research study happens to be the first of its kind in this region and should provide a thrust towards the use of technology-supported classrooms for effectively teaching other school subjects.